Influence of Temperature, pH and selected growth media on germination, growth and sporulation of Aschersonia placenta and Hypocrella raciborskii - Ibrahim, Y. B.; Lim, T. K.; Tang, M. K.; Teng, H. M. (1993)
Tween 70 at 0.1% provided the best conditions for germination of Aschersonia placenta. Optimum germination and growth of the germ tube occurred over a temperature range of 25-30°C and a pH range of 5.0-6.0. A temperature of 30°C resulted in the longest germ tube at 45 pm. Apparently, temperature and pH did not affect the type of germination, with polar germination being consistently recorded for in excess of 60% of conidia. In general, growth and sporulation seemed to be much better in semi-solid than in liquid media. Amongst several plant media tested’, pumpkin consistently gave the most mycelial growth and sporulation. The ability of A. placenta to sporulate on the surface of liquid culture has increased the possibilty of its mass production for the purpose of formulating a microbial pesticide against the indigenous scale insects of tropical fruits such as durian and guava in Malaysia. © 1993, Taylor & Francis Group, LLC. All rights reserved.